Cambridge textbook of neuroscience for psychiatrists - Jones, Peter B. 1960-; Lynall, Mary-Ellen 1986-; Stahl, Stephen M. 1951- (Cambridge University Press, 2024)
Cambridge Textbook of Neuroscience for Psychiatrists is a 'one stop shop' for what any psychiatrist needs to know about the brain. Understanding the brain and mind requires a vast array of techniques and conceptual approaches. The Editors have assembled a team of basic neuroscientists, geneticists, psychologists, psychiatrists, neurologists, neurosurgeons and endocrinologists who bring you the cutting edge of translational neuroscience that addresses the material most relevant to current or future psychiatric practice. The book showcases what is known, highlights aspects that are less well understood and defines key outstanding questions. A revolution in our understanding of the brain has, so far, done little to disrupt mainstream psychiatric practice. That is set to change. The chapters align with the UK MRCPsych neuroscience syllabus and link to the USA National Neuroscience Curriculum Initiative (NNCI). Highly illustrated and accessible, this book will appeal to psychiatrists, neuroscientists, psychologists, other healthcare students and professionals.